2022
DOI: 10.3390/molecules27030691
|View full text |Cite
|
Sign up to set email alerts
|

Chickpeas from a Chilean Region Affected by a Climate-Related Catastrophe: Effects of Water Stress on Grain Yield and Flavonoid Composition

Abstract: The Valparaiso region in Chile was decreed a zone affected by catastrophe in 2019 as a consequence of one of the driest seasons of the last 50 years. In this study, three varieties (‘Alfa-INIA’, ‘California-INIA’, and one landrace, ‘Local Navidad’) of kabuli-type chickpea seeds produced in 2018 (control) and 2019 (climate-related catastrophe, hereafter named water stress) were evaluated for their grain yield. Furthermore, the flavonoid profile of both free and esterified phenolic extracts was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Meanwhile, two MRM transitions were considered and 15 compounds recognized by the molecular and other specific ions. The scanned m/z of compounds coincided with those previously reported in chickpeas [ 21 ] and other legumes [ 34 ].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Meanwhile, two MRM transitions were considered and 15 compounds recognized by the molecular and other specific ions. The scanned m/z of compounds coincided with those previously reported in chickpeas [ 21 ] and other legumes [ 34 ].…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, we did not detect kaempferol in the free phenolic fraction of ‘California-INIA’ and ’Alfa-INIA’. In addition, rutin was found in the soluble fractions in the three evaluated varieties (‘California-INIA’, ’Alfa-INIA’, and ‘Local Navidad’) [ 21 ]. Insoluble-bound kaempferol, rutin, and isorhamnetin were detected in all varieties, but insoluble-bound luteolin was absent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are not aware of previous studies that have examined phytoestrogen response in red clover to experimentally manipulated drought or waterlogging stress; however, de Camargo et al 29 reported cultivars of chickpeas produced up to 3.2 times higher concentrations of biochanin A during a severe drought year compared to a previous year with ample rainfall. 29 Similarly, research conducted on soybeans demonstrated plants grown under mild drought stress increased isoflavone concentration (∼3%) compared to wellwatered plants, 30 and soybean seeds from plants grown under drought stress conditions in growth chambers had elevated levels of genistein compared to seeds from plants grown under the same conditions but with adequate water. 31 Also in line with our findings, greater isoflavone concentration was measured in soybean grain when plants were grown in waterlogged conditions compared to under well-watered conditions.…”
Section: ■ Discussionmentioning
confidence: 93%